Just for kids? How the youth decarceration discourse endorses adult incarceration - Viterbo, Hedi (Criminology & criminal justice, 2025)
This article lays bare three interrelated and previously overlooked pitfalls of calls to reduce or abolish youth incarceration. First, despite their anti-carceral semblance, such calls persistently portray the overwhelming majority of people in trouble with the law—namely, adults—as incorrigible, blameworthy, and therefore as deserving of punishment and imprisonment. Second, this ageist rhetoric often disregards adult vulnerability. Thus, despite adults’ greater medical vulnerability to the COVID-19 disease, it is youth whom some organizations singled out or even called to prioritize for release from prisons during the coronavirus pandemic. Third, at the heart of the youth decarceration discourse are essentialist assumptions about youth, which rest on questionable science and downplay the socially constructed dimension of age differences. All three pitfalls epitomize a dual fault of the child rights discourse more broadly, as evidenced in other contexts: repeatedly lending legitimacy to punitiveness and apathy toward adults while also working to the detriment of children. Doubtless, there are compelling arguments against penal confinement, but it is only decarceration across the age spectrum that can truly challenge carceral thinking—and ageism.